Representações sociais de enfermeiros brasileiros e portugueses sobre o estresse em serviço de urgência - Oliveira, Joana D'arc de Souza (2012)
This study aimed to analyze the social representations of Brazilian and Portuguese nurses on stress in the emergency service. A semi-structured interview and the free word association test, with "stress" as the inductive stimulus, were used as research instruments. Data were collected from 120 nurses, being 60 from an emergency hospital in the city of Natal, Brazil and 60 from an urgency hospital in the city of Aveiro, Portugal. Data from the word association test were analyzed with the EVOC 2002 program, after thematic categorical content analysis, enabling construction of a data bank. Data gathered from the interview were analyzed by ALCESTE 4.8 software. Nurse represent the stress in the urgency department as a generation of physical and mental detrition where adaptation is unsatisfactorily, resulting in the onset of fatigne, irritability, lack of concentration, lack of motivation, pessimism, impaired interpersonal relationship and low productivity. The solution is part of a complex whole, which demands an integrated way of acting that has demanded increasingly professional attitudes based on multidisciplinarity